Epidermal growth factor receptor (EGFR)—tyrosine kinase inhibitors as a first-line treatment for postoperative recurrent and EGFR-mutated non-small-cell lung cancer. (15th October 2021) - Moriya, Tetsuji; Hamaji, Masatsugu; Yoshizawa, Akihiko; Miyata, Ryo; Noguchi, Misa; Tamari, Shigeyuki; Chiba, Naohisa; Miyamoto, Hideaki; Toyazaki, Toshiya; Tanaka, Satona; Yamada, Yoshito; Yutaka, Yojiro; et al.
Abstract: : OBJECTIVES: To clarify survival outcomes and prognostic factors of patients receiving epidermal growth factor receptor (EGFR) - tyrosine kinase inhibitors (TKIs) as first-line treatment for postoperative recurrence. METHODS: A retrospective chart review was performed to identify consecutive patients who received EGFR-TKIs as first-line treatment for postoperative recurrence of non-small-cell lung cancer (NSCLC) harbouring EGFR gene mutations at our institution between August 2002 and October 2020. Therapeutic response, adverse events, progression-free survival (PFS) and overall survival (OS) were investigated. Survival outcomes were assessed using the Kaplan–Meier analysis. The Cox proportional hazards model was used for univariable and multivariable analyses. RESULTS: Sixty-four patients were included in the study. The objective response and disease control rates were 53% and 92%, respectively. Grade 3 or greater adverse events were noted in 4 (6.3%) patients, including 1 patient (1.6%) of interstitial pneumonia. The median follow-up period was 28.5 months (range 3–202 months). The total number of events was 43 for PFS and 23 for OS, respectively. The median PFS was 18 months, and the median OS was 61 months after EGFR-TKI treatment. In multivariable analysis, osimertinib showed a tendency to prolong PFS [hazard ratio (HR) 0.41, 95% confidence interval (CI) 0.12–1.1; P = 0.071], whereas the micropapillary component was significantly associated with shorter OS (HR 2.1, 95% CI 1.02–6.9; P = 0.045). CONCLUSIONS: EGFR-TKIs as first-line treatment appeared to be a reasonable treatment option in selected patients with postoperative recurrent EGFR-mutated NSCLC. Osimertinib and the micropapillary component may be prognostic factors. Abstract : Epidermal growth factor receptor (EGFR) mutations are well-established oncogenic targets for management of advanced-stage non-small-cell lung cancer (NSCLC) [1, 2].